2012
DOI: 10.3174/ajnr.a2950
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tumor Enhancement, Edema,IDH1Mutational Status,MGMTPromoter Methylation, and Survival in Glioblastoma

Abstract: BACKGROUND AND PURPOSE:Both IDH1 mutation and MGMT promoter methylation are associated with longer survival. We investigated the ability of imaging correlates to serve as noninvasive biomarkers for these molecularly defined GBM subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
203
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(232 citation statements)
references
References 48 publications
16
203
3
Order By: Relevance
“…While TP53 mutation status failed to stratify the survival of both PFS and OS. Our result concerning the predictive value of IDH1 and MGMT methylation was in concordance with previous study (Carrillo et al, 2012;Molenaar et al, 2014). Nevertheless, based on the IDH1 wild type status, MGMT promoter methylation could not differentiate the outcome of patients with GBM treated with radiochemotherapy but TP53 mutation status showed predictive effect on the prognostic survival, patients with TP53 mutation experienced a longer PFS and OS than patients without mutated TP53 (p=0.003 for PFS and p=0.029 for OS respectively).…”
Section: Discussionsupporting
confidence: 90%
“…While TP53 mutation status failed to stratify the survival of both PFS and OS. Our result concerning the predictive value of IDH1 and MGMT methylation was in concordance with previous study (Carrillo et al, 2012;Molenaar et al, 2014). Nevertheless, based on the IDH1 wild type status, MGMT promoter methylation could not differentiate the outcome of patients with GBM treated with radiochemotherapy but TP53 mutation status showed predictive effect on the prognostic survival, patients with TP53 mutation experienced a longer PFS and OS than patients without mutated TP53 (p=0.003 for PFS and p=0.029 for OS respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with GBM with MGMT promotor methylation are more responsive to temozolomide therapy and have better clinical outcome than those without it. [27][28][29] Therefore, the detection of IDH1 mutations and MGMT promotor methylation is of great importance for patients with GBM. Carrillo et al 29 suggested that patients with mutant IDH1 have low vascular endothelial growth factor levels, which are associated with contrast enhancement.…”
mentioning
confidence: 99%
“…[27][28][29] Therefore, the detection of IDH1 mutations and MGMT promotor methylation is of great importance for patients with GBM. Carrillo et al 29 suggested that patients with mutant IDH1 have low vascular endothelial growth factor levels, which are associated with contrast enhancement. These findings led to the hypothesis that measurement of tumor vascularity and the necrosis area would be helpful to differentiate IDH1 mutation status.…”
mentioning
confidence: 99%
“…IDH1 R132H mutation overexpression has been shown to decrease cell proliferation (Parsons et al., 2008). Several studies show the presence of the IDH1 R132H mutation in 70–90% of secondary GBMs and 10% primary GBMs, both cases associated with young patients and a higher overall survival rate (Bleeker et al., 2012; Carrillo et al., 2012; Mellai et al., 2011; Weller et al., 2009). The median survival of patients with IDH1 mutation is 3.8 years compared with 1.1 years in patients with wild‐type IDH1 (Parsons et al., 2008).…”
Section: Introductionmentioning
confidence: 99%